An evaluation of the existing guidance services at Holy Cross High School, Kolambugan - Pagente, Mamerta (Animo Repository, 1975)
This study evaluates the guidance services of the Holy Cross High School of Kolambugan, Lanao del Norte. The descriptive research method was employed in the study. Two questionnaires were used to survey and gather data from 118 senior high school students and 14 faculty members. Based on the survey, it was found that both the teachers and the students felt that much was being done in three out of the four services in the present guidance program, namely : information, test and interpretation, and counseling. However, they felt that the career counseling service was provided to a certain extent only. The teachers also agreed that guidance services at Holy Cross High School needed much improvement. Also, the teachers did not have the sufficient qualifications needed for guidance work. However, they expressed feelings of adequacy in doing guidance work because of the seminars they attended, and their attitude towards guidance and counseling was quite satisfactory. In the light of the findings of the study, the following improvements should be undertaken in the guidance program of the school : helping students learn more about themselves, assisting students in developing effective study habits, providing help in subjects where students have difficulties, informing students on how to select a vocation and plan for the future, informing students regarding college entrance requirements after graduation, informing parents about the importance of guidance and counseling in school, helping students understand the meaning of their guidance test scores, and providing a continuous in-service training for the faculty.